1995
DOI: 10.1079/bjn19950023
|View full text |Cite
|
Sign up to set email alerts
|

The voluntary feed intake of pigs given feeds based on wheat bran, dried citrus pulp and grass meal, in relation to measurements of feed bulk

Abstract: Two experiments were carried out to investigate the capacities of pigs for bulky feeds. In Expt 1 fifteen pigs were offered, from 12 to 25 kg live weight, ad lib. access to one of five feeds which were made by progressively diluting a high-quality feed with wheat bran. Intake initially increased, and then declined, as the proportion of wheat bran was increased. The pigs became better able to accommodate to the more bulky feeds over time. In Expt 2 thirty& pigs, initially of 12 kg live weight, were used. The fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
2
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 15 publications
(14 reference statements)
8
117
2
3
Order By: Relevance
“…High levels of CF were found to result in an increase in FCR, in agreement with previous work (Asmus et al, 2014). However, it is also important to consider that there was a high negative correlation between ME and CF, which may also explain this finding; the lower energy density of high CF diets necessitating a greater daily intake (Kyriazakis and Emmans, 1995). Improved feed efficiency, that is, lower FCR, was found for higher lysine and CP feed content, which is consistent with previous literature (Kyriazakis et al, 1991;Szabó et al, 2001).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…High levels of CF were found to result in an increase in FCR, in agreement with previous work (Asmus et al, 2014). However, it is also important to consider that there was a high negative correlation between ME and CF, which may also explain this finding; the lower energy density of high CF diets necessitating a greater daily intake (Kyriazakis and Emmans, 1995). Improved feed efficiency, that is, lower FCR, was found for higher lysine and CP feed content, which is consistent with previous literature (Kyriazakis et al, 1991;Szabó et al, 2001).…”
supporting
confidence: 89%
“…The effect of ME content on FI demonstrates the consequence of low ME levels on the intake of pigs (Kyriazakis and Emmans, 1995;Whittemore et al, 2002); the only exception being the lower FI of pigs on higher ME level at the lowest space allowance. This probably reflects the increased competition at the feeder, which is absent when pigs are given access to bulky feeds (Whittemore et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Nesta pesquisa, somente Lisina-HCL foi adicionada para obter o mesmo nível do aminoácido digestível em todas as dietas. Kyriazakis & Emmans (1995) relataram que, ao incluírem altos teores de fibra nas rações, pode ocorrer menor consumo de ração, como conseqüência do volume excessivo no trato intestinal ou da redução na palatabilidade. Segundo Kass et al (1980a), níveis de fibra bruta de 7 a 10% na dieta têm efeito negativo sobre o desempenho de suínos em crescimento e a extensão desse efeito depende da fonte e do tipo de fibra.…”
Section: Resultsunclassified
“…We have not found any differences in ep between male and female pigs of a genotype of pig (Kyriazakis & Emmans, 1992b,c) on a given limiting diet, or between the pigs of two very different breeds (Kyriazakis et al 1994;Kyriazakis & Emmans, 199%). Similarly, Noblet et al (1992) have found no differences in ep between control and somatotropin-treated pigs, given the same food allowances which were limiting for both.…”
Section: A P a R T I T I O N I N G R U L Ementioning
confidence: 76%